Optimization Process of Virgin Coconut Oil Production to Meet The Quality of Lulur Cosmetics (Balai Riset dan Standardisasi Industri Pontianak, 2010)
Optimization process of virgin coconut oil (VCO) production to meet the quality of lulur cosmetics was carried out in the Institute for Industrial Research and Standardization Pontianak. This research aimed to increase the productivity of pure coconut oil both quantity nor quality that were produced so it can meet the quality characteristics as raw material of lulur cosmetic. This research was use coconut and pineapple in a local species as the main raw material and other supporting materials such as VCO and others. There were 2 (two) treatment factor used namely A (bromelin extract volume) and B (mixing time). The parameters observed were water content, acid number, saponification number, and free fatty acid (FFA). Results showed that the treatment without bromelin extract with 5 minutes mixing time were the best treatment for raw material of lulur cosmetic, with the water content 0.122%, the free fatty acid 0.062%, the acid number 0.174, and saponification number 261,21 (the condition for oil as the cosmetic raw material was 0.2% max.).